Prevalence of hypovitaminosis D in institutionalized elderly - Caleffi Paiva, Cezar Augusto; Bettinelli, Luiz Antonio; Pasqualotti, Adriano; Dobner, Taise; Pasqualotti, Pablo (O Mundo da Saúde, 2017)
Vitamin D deficiency affects approximately one billion people around the world, making it a public health problem. It causes changes in growth and bone development in children and osteomalacia and osteoporosis in adults and elderly. Vitamin D makes possible normal bone mineralization and bone calcium mobilization into the blood. The deficiency of it increases the risk of falls in the elderly and, consequently, the risk of fractures and/or other health problems. Considering the information presented, the prospective cross-sectional study with probability sampling, aimed to determine the prevalence of hypovitaminosis D in institutionalized elderly in Passo Fundo/RS. 77 elderly patients participated in the study. The levels of 25-hydroxyvitamin D were measured and were associated with the socioeconomic and demographic data, medication and daily habits. The data were collected between June to August 2011. There was a prevalence of hypovitaminosis D among 97% of the sample. A noticeable deficiency of vitamin D was only statistically associated with albumin levels (p = 0.048). It was also evident that there was a negative correlation between the serum levels of 25 (OH) D and the parathyroid hormone PTH (rs = -0.240, p = 0.033). There is a high prevalence of hypovitaminosis D among institutionalized elderly. Health professionals and caregivers should take interdisciplinary measures that minimize this public health problem.